Optimizing feed frame design and tableting process parameters to increase die-filling uniformity on a high-speed rotary tablet press - Grymonpré, W; Vanhoorne, V; Van Snick, B; Blahova Prudilova, B; Detobel, F; Remon, J P; De Beer, T; Vervaet, C (International journal of pharmaceutics, 2018)
Despite the high quantities of tablets produced daily, many tableting processes are still operated at sub-optimal settings and hence lack the necessary flexibility to mitigate for possible process deviations. However, to ensure this flexibility on tableting throughput it is important to select the most robust feed frame design and settings regarding die-filling. In this research study, four paddle designs for a two-compartment forced feeder (equipped with a metering and a feeding paddle wheel) were evaluated at a wide range of process-settings (i.e. tableting speed, paddle speed, overfill level) and feed frame features (i.e. deaeration) for their impact on the die-filling step of a poorly flowing model formulation (i.e. MCC 101) using a quality-by-design approach. No benefit on die-filling was observed when using higher speeds of the metering paddle wheel compared to the feeding paddle wheel, and no convincing arguments were obtained to use the feed frame deaeration opening. Some combinations of paddle design and process-settings significantly increased the risk for inconsistent die-filling (i.e. high tablet weight variability) which can therefore limit the efficiency of the tableting process. The approach used in this study enabled to compare the paddle designs for their die-filling performance in function of varying tableting speeds, eventually resulting in the selection of a feed frame design that is most robust and therefore will provide a uniform die-filling over a wide range of throughputs. Selection of the most robust parameters is an important prerequisite for the ability of using the rotary tablet press as an agile unit-operation.
Keywords: Paddle design; Quality-by-design (QbD); prášky, zásypy, pudry; příprava léků; Continuous tablet manufacturing; Process-engineering; Drug Compounding; celulosa; Powders; Hardness; Cellulose; Tablets; Direct compression; tvrdost; tablety; Forced feeders